2017
DOI: 10.5546/aap.2017.eng.35
|View full text |Cite
|
Sign up to set email alerts
|

Bullying at school: Agreement between caregivers’ and children’s perception

Abstract: Introduction. Bullying at school is usually kept secret from adults, making them unaware of the situation. Objective. To describe caregivers' and children's perception and assess their agreement in terms of bullying situations. Methods. Cross-sectional study in children aged 8-12 years old attending public schools and their caregivers. The questionnaire on preconceptions of intimidation and bullying among peers (PRECONCIMEI) (child/caregiver version) was used. Studied outcome measures: Scale of bullying, cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…It appears that children are likely more prone to disclose or be open about their victimization experiences vis-à-vis their parents than about bullying perpetration, mirroring results in other studies [ 13 ]. Moreover, our findings largely resonate with previous studies in the field that have robustly reported low levels of agreement between parent- and child-reports of peer bullying [ 13 , 19 , 20 , 21 , 22 , 23 ]. As such, our results support the notion that scholars should employ a multi-informant approach in future studies on bullying [ 28 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…It appears that children are likely more prone to disclose or be open about their victimization experiences vis-à-vis their parents than about bullying perpetration, mirroring results in other studies [ 13 ]. Moreover, our findings largely resonate with previous studies in the field that have robustly reported low levels of agreement between parent- and child-reports of peer bullying [ 13 , 19 , 20 , 21 , 22 , 23 ]. As such, our results support the notion that scholars should employ a multi-informant approach in future studies on bullying [ 28 ].…”
Section: Discussionsupporting
confidence: 88%
“…One common way of assessing the extent to which parents are aware of their children’s bullying involvement is to explore the agreement across child- and parent-reports of bullying. Studies have robustly found low rates of parent-child agreement in the general population [ 13 , 19 , 20 , 21 , 22 , 23 ] as well as in clinical samples [ 24 ]. Agreement levels were higher for victimization as compared to perpetration, suggesting that children may be more likely to talk to their parents about their victimization experiences [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that only the more severe episodes of racism will be reported by children to their parents, which again, would contribute to underestimating racism exposure. Although caregivers believe their children would tell them about bullying/victimization at school, children who suffer discrimination refer not telling their caregivers about such experiences [57]. Therefore, future research should seek to understand experiences of racism from the child’s perspective and across all contexts [13].…”
Section: Discussionmentioning
confidence: 99%
“…The role of parents in identifying and addressing the issue of bullying in their children is important. Few studies pointed out that parents may be unaware that their children are being bullied [ 21 ]. However, this may not be the case with all populations.…”
Section: Introductionmentioning
confidence: 99%